Pemahaman Kebutuhan Kasih Sayang pada Pasangan: Perspektif Psikologi - Nurjanis (Indra Institute Research & Publication, 2024)
Love is a fundamental need in a couple's relationship that not only affects the quality of marital life but also the psychological well-being of individuals. This study aims to understand how couples perceive and fulfill the need for love in their relationship, as well as its impact on marital harmony, from a psychological perspective. Using a qualitative method, in-depth interviews were conducted with 20 couples who have been married for more than three years. The results show that couples who understand and meet each other's love needs have better communication, more harmonious relationships, and greater resilience to conflicts. Furthermore, the study identifies the importance of emotional communication and empathy in maintaining relationship stability. These findings provide insight into how fulfilling the need for love can strengthen long-term relationships.